Deteksi Residu Antibiotik Oxytetracycline pada Hati Ayam Broiler di Pasar Tradisional Mandalika Mataram - Nina Mardiana; Ni Luh Lasmi Purwanti; Candra Dwi Atma; Iwan Doddy Dharmawibawa (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to detect the presence of Oxytetracycline antibiotic residues in broiler chicken livers sold at the Mandalika Traditional Market, Mataram City. This study used a bioassay screening test method to detect antibiotic residues in broiler chicken liver samples taken from 10 traders in the market. The results showed that no antibiotic residues were found in all samples tested. All samples showed negative results, which means that the broiler chicken livers sold in the market contain Oxytetracycline residues. Based on these findings, it can be concluded that broiler chickens sold at the Mandalika Traditional Market do not contain Oxytetracycline antibiotic residues that exceed the safe limit for consumption.